Análise térmica de diferentes armazéns (convencional, climatizado e com forro de alumínio) na armazenabilidade de sementes de soja (Glycine max (L.) Merrill) - Suguiy, Mary Mieko Tateiwa (2005)
The soybean culture [Glycine max (L.) Merril] has great economical importance in the Brazilian agricultural scenery, in which the seed the production contributed significantly to this process. The environmental conditions of the storerooms such as, relative humidity and temperature affect the speeds longevity and vigor. The physiology quality of seeds needs to be determined not only at the harvesting or processing but also during the storage period. Handing practices may contribute to accelerate the seeds deterioration, during the crop and processing, leading to the decrease of the storage period. The present work aimed to evaluate the quality of 12 month storage of soybean seeds in three treatment storerooms as follows: T1 no foil (conventional), T2 one lining of foil and T3 no foil with cooling system. The temperature of black globe (TG) and the Black Globe Humidity Index (BGHI) were used as parameters for evaluation of the thermal atmosphere of the stored seeds. It was evaluated the vigor, by accelerated aging and tetrazolium test, and germination at 0, 60, 120, 180, 240 and 360 days after the storage process. It was observed that there were significant differences in the germination values and vigor of the soybean seeds stored in the systems T3 in relation to T1 and T2. The climatic indexes (TG and BGHI) of all systems did not differ statistically